Experiences in outpatient parenteral antimicrobial therapy (OPAT): Barriers and challenges from the front lines - Nicole Ng; Pamela Bailey; Rachel Pryor; Lillian Fung; Christine Veals; Kenneth Sabouri; Julie Reznicek (Cambridge University Press, 2021)
Abstract Background: Outpatient parenteral antimicrobial therapy (OPAT) is now the standard of care for managing patients who no longer need inpatient care but require prolonged intravenous antimicrobial therapy. OPAT increases patient satisfaction, reduces the lengths of hospital stay, lowers emergency department readmission rates, and decreases total healthcare spending. Objective: To investigate Virginia Commonwealth University Health System's experience with OPAT and to highlight the obstacles patients and clinicians face when navigating and utilizing this program. Design: We conducted this descriptive study at a large, academic, tertiary-care hospital in Central Virginia. Methods: We performed manual reviews of electronic medical records of 602 patient, and we evaluated the records of those receiving OPAT between 2017 and 2020. Reviews included antimicrobial agents, diagnoses requiring OPAT, adverse effects related to antimicrobials, adverse effects related to peripherally inserted central catheters (PICC), readmission rate, discharge destination, and death. We evaluated our program with descriptive statistics. Results: Among 602 patients who received OPAT, most were diagnosed with bacteremia or musculoskeletal infections. Patients were either discharged home or to another healthcare facility, with the former comprising most of the rehospitalizations. Ertapenem and vancomycin were associated with the most adverse drug events among our cohort. Elevated transaminase levels were noted in 23% of patients. The rate of PICC-line adverse events in this study population was 0.05%. Conclusions: Our findings highlight the barriers and challenges that patients and providers face when receiving OPAT, and they can inform efforts to improve patient clinical outcomes.